A descriptive study on the knowledge, attitudes and practices of private dental practitioners in Malate, Manila on the handling, storage and disposal of used sharps - Lucar, Rochell D.; Talde, Catherine Joy C.; Galban, Angelita A. (Adviser).
Health care waste management is a concern which need to be focused on due to the adverse effects these wastes may harbour to the environment and to the people. However, as what is observed in the country, implementation of the laws and guidelines on the management of infectious wastes is usually not carried out strictly and effectively. This study generally aims to determine the knowledge, attitudes and practices of private dental clinics in Malate, Manila on the handling, storage and disposal of their used sharps. This study also intend to determine the frequency of sharps use, the different techniques used in handling, storage and disposal of sharps wastes, the level of knowledge and training of the dentist in the dental clinic on the proper handling and disposal of sharps and whether vaccinations (eg. Hepatitis B vaccine) are done as a preventive measure in the management of sharps. This study also would like to determine the awareness of the policies and regulations on sharps disposal issued by the DOH and MMDA, if each clinic allots a budget and time for the disposal of used sharps before being taken by the waste collectors and to identify, if there's any, agencies called on by the dental practitioners in the final disposal of sharps. The subjects of the study are all private dentists practicing in Malate, Manila. Non-functional clinics (such as those which are constantly closed or vacant) are excluded in the study. All in all, the researchers found 82 private dental clinics, 9 of which are vacant. Six of these 82 clinics were not given the questionnaire because they were constantly closed. Therefore, only 67 private dental clinics were given the survey questionnaire and only 36 responded. The data gathered was subjected to descriptive statistics. The data was encoded by the biostatistician using Epi Info, and the data file was tabulated and subjected to Microsoft Excel. The knowledge, attitudes and practices of private dental clinics in Malate, Manila on the management of used sharps were analysed and the researchers found out that Private dental clinics in Malate, Manila generally use sharps 1-3 times a week. The most frequently used sharps are anesthetic carpules and burs. They have an average of 6-10 cases a week which require the use of anesthesia. Majority (53%) of the dentists do not perform pre-treatment procedures on their used sharps prior to final disposal. Entombing sharps in plaster of Paris or cement gained the highest percentage when the dentists were asked about the techniques they use in the management of their used sharps. Majority (63.89%) of the dentists have regular shots of vaccines, specifically Hepatitis vaccines and anti-tetanus vaccines. For dentists who have staff, equal percentages of 36.11% replied that they require or do not require their staff to have vaccinations against infectious diseases for reasons that they don't allow them to perform dental procedures. For others, the matter about vaccination of their staff is optional. Majority (52.78%) of the dentists are aware of the biomedical waste guidelines, with the Center for Disease Control being the most known to them. They claimed to have been aware of the said guideline through seminars and own readings. These dentists also train their dental staff on infection control procedures, but do not necessarily require them to attend seminars on infection control. Majority (59%) of the dentists do not allot a budget for the management of their used sharps prior to final disposal and collection by waste collectors. A number of dentists (21%) claimed to have called on waste management agencies for the disposal of their sharps waste, however, when asked to identify the agency, there were no response. Two of the dentists have claimed to bring their sharps to the nearest hospitals where the wastes are to be incinerated. This study revealed that private dentists practicing in Malate, Manila are highly aware of the biomedical waste management guidelines, specifically those of the international monitoring guidelines, however, this is not otherwise reflected in their attitudes and practices on sharps management. Instead, they tend to modify the said guidelines for purposes of practicality in terms of time and budget.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental waste; Cross infection; Waste management